Diagnosis of the environmental perception of the communities surrounding La Libertad Metropolitan Park, San José, Costa Rica - Barboza-Guzmán, Raymond (2013)
This diagnosis was performed in order to obtain information of the major social and environmental communities bordering the Parque Metropolitano La Libertad, located in San José. These communities are Fátima, Patarrá, Linda Vista and Río Azul. The information obtained will help the development of an environmental education plan according to major environmental and social problems of communities, these projects require awareness programs to promote changes in the population in the short, medium and long term, which in turn required to be justified by diagnostic information on the problems and perceptions that these communities have on the environment in which they operate.